Comparison of Side to Side Staple Versus Hand Sewn Gastro Esophageal Anastomosis in Cases of Oesophagectomy in CA Esophagus - Khan, Mohammad Abid; Baseer, Abdul; Aslam, Tahir; Aslam, Viqar; Ahmed, Asif (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare outcomes of side to side staple versus hand-sewn esophago-gastric anastomosis in esophagectomy patients with carcinoma of esophagus after subtotal esophagectomy along with gastric tube reconstruction.Study Design: Retrospective cross-sectional study.Place and Duration of Study: Lady Reading Hospital, Peshawar Pakistan, from July 2019 to June 2020.Methodology: After ethical approval, medical records of patients that underwent stapled/hand sewn gastro esophageal anastomosis due to carcinoma esophagus were included. Inoperable Ca esophagus and with thoracic anastomosis were excluded. Each anastomotic technique was applied on 50 patients randomly. The variables of study included demographic,anastomotic leak, anastomotic stricture, operative time, and other complications. All the cases were followed up for 1 year.SPSS version 26.0 was used for data analysis.Result: From 100 patients, 56 were males and 34 females. Age ranged from 15 to 80 years with mean age of 48.5 and 51.1 respectively in two groups. In 42 cases tumor was present in lower end, middle third in 30 and middle lower third of gastro esophageal junction in 28 cases. Histo-pathologically 58 cases were adenocarcinoma, 31 squamous cell carcinoma and 11 adeno squamous carcinoma. The anastomosis time in group I was 6.8±.22 minutes while in group II was 13.2±1.71 minutes (p0.04). None of the patients in group I, having stapled anastomosis were found to have anastomotic leakage or stricture formation after 1 year of follow up while 04 patients in group II were reported to have anastomotic leakage and 06 patients had anastomotic stricture formation (p-